Study guides

☆☆

Q: What is 1 divided by 1 plus the square root of 3?

Write your answer...

Submit

Still have questions?

Related questions

It is: 1+1+8 = 10

a quarter is 1/4 and square root of 1/4 is square root (1/4)=square root of 1 divided by square root of 4 which is 1 divided by 2. So the answer is 1/2

1 plus (6 divided by ((square root of 9) plus (square root of 9))) or 9/(9-6)-1=2

0.1111

Square root 1/483 = .0455

square root of (x2 + 1) = no simplification (square root of x2) + 1 = x + 1

0.0278

wow u cant figure out awnser relly the At first you will multiply the, (1 divided by 2 square root of 2) by (2square root of 2 divided by 2 square root of 2) because 2 square root of 2 is irrational. so the answer is square root of 2 over 4.

8.1667

X^1/2 + Y^1/2 Essentially it is just the square root of x plus the square root of y, there's no real way of simplifying that.

2

9

Yes, if x and y = 1 √1 + √1 = √1 + 1 1 + 1 = 1 + 1 QED

Square root of 3 is approximately 1.732. 1.732 + 1 =2.732

-100

That doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (-1 plus or minus the square root of -139) divided by 2.x = -0.5 + 5.894913061275798ix = -0.5 - 5.894913061275798iwhere i is the square root of -1.

That doesn't factor neatly. Applying the quadratic formula, we find 2 imaginary solutions: (-1 plus or minus the square root of -83) divided by 2x = -0.5 + 4.55521678957215ix = -0.5 - 4.55521678957215iwhere i is the square root of -1.

1

0.1667

1

0.25

√75 + √147 = 20.7846097

That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-1 plus or minus the square root of -3) divided by 2.x = -0.5 + 0.8660254037844386ix = -0.5 - 0.8660254037844386iwhere i is the square root of negative one.

5

x2+3i=0 so x2=-3i x=square root of (-3i)=square root (-3)square root (i) =i(square root(3)([1/(square root (2)](1+i) and i(square root(3)([-1/(square root (2)](1+i) You can multiply through by i if you want, but I left it since it shows you where the answer came from. Note: The square root of i is 1/square root 2(1+i) and -1/square root of 2 (1+i) to see this, try and square them!